Effect of Ti–Cu alloy's composition on microstructure and performance of carbon fiber reinforced TiC-based composites prepared by alloyed reactive melt infiltration. Issue 20 (15th October 2022) - Tong, Yonggang; Wang, Bin; Hu, Yongle; Hua, Manyu; Han, Kun; Shen, Hongji; Zhang, Peng; Li, Yang
Abstract: In order to improve the strength and toughness of ceramic matrix composites, carbon fiber reinforced TiC-based composites modified with Cu based alloys were fabricated by alloyed reactive melt infiltration method using Ti27 Cu73, TiCu and Ti2 Cu alloys as infiltrators. The effects of Cu content on the composite's microstructure, mechanical strength and tribological properties were respectively investigated. The as-produced composites were mainly composed of C, TiC, Cu and Ti–Cu phases. With the decrease of Cu content in the infiltrated alloys, more TiC matrix was produced in the composites. The composites prepared with the infiltrators with high Cu contents exhibited enhanced mechanical properties. The composites prepared by Ti27 Cu73 alloy owned the largest strength of 294.73 ± 23.91 MPa, while the composites prepared by TiCu alloy had the best fracture toughness of 14.36 ± 1.42 MPa m 1/2 . The as-produced composites exhibited good wear resistance. A Cu based friction layer was observed on the friction trace due to the introduction of Cu based alloy matrix into the composites, which greatly improved the abrasive performance.